2013
DOI: 10.1080/13803395.2013.806649
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between executive functioning, processing speed, and white matter integrity in multiple sclerosis

Abstract: The primary purpose of the current study was to examine the relationship between performance on executive tasks and white matter integrity, assessed by diffusion tensor imaging (DTI) in Multiple Sclerosis (MS). A second aim was to examine how processing speed affects the relationship between executive functioning and FA. This relationship was examined in two executive tasks that rely heavily on processing speed: the Color-Word Interference Test and Trail-Making Test (Delis-Kaplan Executive Function System). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 40 publications
6
44
0
Order By: Relevance
“…The analysis of regional trends further corroborated our hypothesis by demonstrating that reduced integrity of associative, rather than motor and sensory, WM regions may explain the processing speed deficits in both groups. This is consistent with previous research showing that the integrity of associative WM fibers that carry multimodal, higher order functional information, is critical for maintaining normal speed of information processing [Borghesani et al, ; Genova et al, ; Kochunov et al, ; Llufriu et al, ; Peters et al, ]. R WM/GM appeared to be specifically associated with processing speed.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of regional trends further corroborated our hypothesis by demonstrating that reduced integrity of associative, rather than motor and sensory, WM regions may explain the processing speed deficits in both groups. This is consistent with previous research showing that the integrity of associative WM fibers that carry multimodal, higher order functional information, is critical for maintaining normal speed of information processing [Borghesani et al, ; Genova et al, ; Kochunov et al, ; Llufriu et al, ; Peters et al, ]. R WM/GM appeared to be specifically associated with processing speed.…”
Section: Discussionsupporting
confidence: 91%
“…[29][30][31][32][33] Sigal et al [11] used DTI to investigate CC integrity in MS patients and age matched controls. In agreement with other studies, [15,26,28,31] MS patients had significant reduction in CC 's FA compared with control group in all subregion of CC, indicating axonal loss and dysfunction in callosal fibers. Most recent studies agree on the fact that in MS patients all MRI indices and parameters are altered pathologically especially in the CC structure.…”
Section: In Multiple Sclerosis Mrisupporting
confidence: 80%
“…There are also some other parameters in the matter of directional diffusivity such as: radial and axial diffusivity, which have been used by many recent studies. [15,25,26,28] Such parameters interestingly found to be helpful in detecting microscopic and structural changes in lesional and NAWM. Most of recent studies showed increased ADC and reduced FA in both pathologic and NAWM.…”
Section: In Multiple Sclerosis Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…White matter results indicated decreases in EF behavior relating to putting order into work and play (Plan/Organize subscale) was associated with decreased FA in the forceps minor. Research demonstrates the forceps minor is a fiber bundle which connects the lateral and medial surfaces of the frontal lobes and crosses the midline via the genu of the corpus callosum (Genova, DeLuca, Chiaravalloti, & Wylie, ). When damaged by disease, the forceps minor is linked to robustly diminished processing speed and cognitive impairment, indicating its interhemispheric connections between the PFC contribute to EF (Biesbroek et al, ; Genova et al, ).…”
Section: Discussionmentioning
confidence: 99%